Uji Aktifitas Antioksidan, flavonoid Total dan Formulasi Sediaan Krim Ekstrak Bangle (Zingiber cassumunar) - Lailiyah, Munifatul; Andika Saputra, Sony; Aryantini, Dyah (Indonesian Journal of Pharmaceutical Education, 2024)
Bangle rhizome (Zingiber cassumunar) is a plant with essential oil, flavonoid, and curcumin content which is efficacious as a traditional medicine and has antioxidant activity. The purpose of this study was to determine the antioxidant activity and test the total flavonoid content contained in the rhizome extract (Zingiber cassumunar) using UV-Vis spectrophotometry. Then a cream preparation was made and tested for physical quality including, organoleptic, homogeneity, pH, adhesive power, and spreadability. The extraction method uses the maceration method of bangle rhizomes (Zingiber cassumunar) using an alcohol solvent until a thick extract is obtained, then a quantitative test is carried out for the content of total flavonoid compounds in the form of determining total flavonoid levels and free radical scavenging activity using the DPPH method. The results showed that the bangle rhizome extract (Zingiber cassumunar) had a yield value of 26.25%. The extract of bangle rhizome (Zingiber cassumunar) has a total flavonoid value of 86.7±0.4 mg QE/g extract, which means it contains high flavonoid compounds and has an IC50 value of 48.29±7.9 (µg/mL) with a powerful category. The physical quality test of the three formulations meets the criteria for physical quality test requirements. The total flavonoid compound content value in the 96% ethanol extract of bangle rhizome (Zingiber cassumunar) is 86.7 mg QE / g extract which means it contains high flavonoid compounds. The IC50 value of the 96% ethanol extract of bangle rhizome (Zingiber cassumunar) is 48.29µg/mL which means it has extreme free radical scavenging activity. Formulations, 1, 2, and 3 meet the physical quality test.